INTERRELATION OF FEEDBACK AND MOTIVATION IN ASSESSMENT OF STUDENTS (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
This article is devoted to the study of the impact of feedback on students’ success in foreign language acquisition, with the aim of identifying how different types of feedback influence learning outcomes. The research involved both quantitative and qualitative methods, including surveys and classroom observations conducted among university students learning foreign languages. The results revealed that timely and constructive feedback significantly contributes to the development of speaking, writing, and comprehension skills. According to survey data, 60% of students reported that feedback helped them better understand their mistakes, and 25% said it increased their motivation to improve. However, 15% of respondents indicated that overly critical feedback could cause anxiety and reduce confidence. The findings suggest that feedback plays a crucial role in language learning success, not only by guiding students but also by shaping their motivation and engagement. Therefore, implementing balanced, supportive feedback practices can enhance language acquisition and foster a positive learning environment.